Influence of Religion in Politics: A Comparative Analysis of 2023 Nigerian and 2024 American Presidential Elections - Nwaozuru Johnmajor Chinecherem (Asian Journal of Islamic Studies and Da'wah, 2026)
Religion continues to play a significant role in contemporary democratic politics, particularly in religiously plural societies where electoral behavior is often shaped by faith-based identities and appeals. This study examined the influence of religion in the 2023 Nigerian and 2024 United States presidential elections, with particular attention to how selected candidates deployed what this study terms “religio-political strategies” during their campaigns to attract electoral support. Using a qualitative research approach, the study drew on both primary and secondary sources of data, including observation, books, journal articles, newspapers, magazines, previous project materials, and internet documentary reports relevant to the elections under review. The findings indicate that religion remained an influential factor in both electoral contexts, as candidates such as Peter Obi and Bola Ahmed Tinubu in Nigeria and Donald Trump in the United States employed religiously inflected campaign strategies to appeal to the electorate. These strategies generated substantial support for their presidential bids, and some of the candidates who adopted them secured electoral victory. The study concludes that religion continues to shape modern political processes and remains highly relevant to electoral mobilization in democratic societies. It contributes to the growing discourse on religion and politics by demonstrating how religio-political strategies can influence voter alignment and election outcomes in pluralistic states, while implying the need for more critical engagement with the intersection of faith and democratic participation, particularly in Nigeria.